Vegetation Type and Age Drive Changes in Soil Properties, Nitrogen, and Carbon Sequestration in Urban Parks under Cold Climate - Setälä, Heikki M.; Francini, Gaia; Allen, John A.; Hui, Nan; Jumpponen, Ari; Kotze, David J. (Frontiers in Ecology and Evolution, 2016)
Urban green spaces provide ecosystem properties fundamental to the provision of ecosystem services, such as the sequestration of carbon and nutrients and serving as a reservoir for organic matter. Although urban vegetation influences soil physico-chemical properties, it remains unknown whether ecosystem properties depend on plant species portfolios. We tested the influence of three common functional plant groups (evergreen trees, deciduous trees, grass/lawn) for their ability to modify soils in parks of various ages under cold climatic conditions in Finland. We hypothesized that (i) plant functional groups affect soils differently resulting in divergent ecosystem properties, and (ii) that these ecosystem properties also depend on park age. We included 41 urban parks of varying ages (10, 50 and > 100 years) and additional control forests. Park soils were sampled for physico-chemical parameters up to 50 cm depth. Our data indicate that plant functional groups modify soils differently, especially between the evergreen and lawn treatments at 50 and > 100 year old parks. Soils under evergreen trees had the lowest pH and generally the highest percentage organic matter, percentage total carbon and percentage total nitrogen. Soil pH remained the same, whereas concentrations of organic matter, total carbon and total nitrogen declined by depth. Soils in the reference forests had lower pH but higher percentages organic matter, total carbon and total nitrogen than those in parks. We estimate that old parks with evergreen trees can store 35.5 kg C m-2 and 2.3 kg N m-2 – considerably more than in urban soils in warmer climates. Our data suggest that plant-soil interactions in urban parks, in spite of being constructed environments, are surprisingly similar to those in natural forests.